"No Need for Nudism": Children's Clothing in the United States, 1940 to 1945. (3rd July 2019) - Mower, Jennifer M.
Abstract : This study explores the influence of World War II on the United States infant and children's clothing industries. Relying on the federal records of the Office of Price Administration's Apparel Enforcement Division, periodicals, extant objects, and photographs, this study concludes that general military requirements of textiles and a spike in births, coupled with federal wartime policies, resulted in shortages of infant and children's wear throughout the United States. Even with these shortages, consumers, mostly mothers, were expected to make do. This study also explores the influence of war on infant and children's dress and strategies recommended to and employed by wartime mothers to upcycle worn-out clothes. The research sheds light on wartime culture and social expectations of mothers with a nation at war.